A Tool for Assessing the Quality of Life of Adolescents in Youth Care: Psychometric Properties of the QOLYSS - Chris Swerts; Marco Lombardi; Laura E. Gómez; Dries Verlet; Dries Debeer; Jessica De Maeyer; Wouter Vanderplasschen (Psychosocial Intervention, 2023)

(untitled)
Quality of life (QOL) has gained increased interest as a critical pathway to better understanding the lives and circumstances of children and adolescents in both the general population and among specific populations. Yet, QOL assessment among youngsters in youth care services remains a highly under-researched topic. This study examines the suitability and psychometric properties of a new QOL self-report scale for adolescents between 12 and 18 years old in youth care: the Quality of Life in Youth Services Scale (QOLYSS). The provisional version of the QOLYSS was pre-tested in a sample of 28 adolescents in youth care to examine its applicability and feasibility. Next, a comprehensive evaluation of the psychometric properties of the field-test version was conducted in a sample of 271 adolescents in youth care in Flanders, Belgium (M = 15.43, SD = 1.73). Classical item and factor analyses were carried out per subscale, (test-retest) reliability and item-discriminant validity of the subscales were examined, convergent validity was explored, and confirmatory factor analysis was used to examine the goodness-of-fit of different measurement models. Reliability measures of the scale are satisfactory, results are indicative of convergent validity, and confirmatory factor analysis provides evidence for the eight correlated factors model. Future lines of research concerning the ongoing development and application of the QOLYSS are discussed.